GAMBARAN HISTOLOGIK GINJAL HEWAN COBA POSTMORTEM - Rahmadana, Baldatun; Wangko, Sunny; Kalangi, Sonny J. R. (Universitas Sam Ratulangi, 2014)
Abstract: Estimation of postmortem interval plays some significant roles in medicolegal investigation. This was a descriptive experimental study using one local pig as model. Samples were taken from the right and left kidneys at several time intervals: 0 minute, 15 minutes, 30 minutes, 45 minutes, 60 minutes, 12 hours, and 24 hours postmortem. The results showed several histological changes, as follows: hydrophic degeneration in a small part of proximal tubules 30 minutes postmortem that increased after 45 minutes associated with narrowing of Bowman cavities; necrosis of glomeruli and proximal tubules associated with irregular distal tubular lumen and widening of Bowman cavities 60 minutes postmortem; necrosis of distal tubuli 12 hours postmortem; and necrosis of most kidney structures 24 hours postmortem. Conclusion: Hydrophic degeneration of proximal tubuli is the earliest histological change 30 minutes postmortem, followed by necrosis of glomeruli as well as proximal and distal tubuli that worsened after 24 hours postmortem. It is expected that this study can provide valuable contribution to medicolegal investigation, especially in early postmortem interval estimation.Keywords: postmortem interval, histological changes, postmortem, kidneyAbstrak: Penentuan saat kematian sangat penting dalam penyelidikan medikolegal. Penelitian ini merupakan penelitian deskriptif-eksperimental dengan menggunakan satu ekor babi lokal sebagai obyek penelitian. Sampel diambil dari ginjal kanan dan kiri pada beberapa interval waktu; 0 menit; 15 menit; 30 menit; 45 menit; 60 menit; 12 jam; dan 24 jam postmortem. Hasil penelitian memperlihatkan degenerasi hidropik pada sebagian kecil tubuli proksimal 30 menit postmortem yang meluas setelah 45 menit disertai penyempitan kavum Bowman; pelebaran kavum Bowman, nekrosis glomeruli dan tubuli proksimal, lumen sebagian kecil tubuli distal ireguler 60 menit postmortem; nekrosis tubuli distal 12 jam postmortem; dan nekrosis hampir seluruh struktur-struktur tersebut 24 jam postmortem. Simpulan: Degenerasi hidropik tubuli proksimal merupakan perubahan histologik yang paling dini yaitu 30 menit postmortem, disusul oleh tanda-tanda nekrosis pada sebagian kecil glomeruli dan tubuli proksimal serta nekrosis tubuli distal yang meluas setelah 24 jam postmortem. Penelitian ini diharapkan dapat memberikan kontribusi yang bermakna untuk kepentingan medikolegal, terutama dalam perkiraan saat kematian dini.Kata kunci: saat kematian, perubahan histologik, ginjal